The Reliability of Diagnosing Schizophrenia Using the GRU Layer in Conjunction with EEG Rhythms - Pankaj Kumar Sahu; Karan Jain (Frontiers in Biomedical Technologies)
Purpose: At resting state, the human brain releases cycles of Electroencephalography (EEG), which has been proven aberrant in persons with schizophrenia. Deep learning methods and patterns found in EEG of brain activity are helpful features for verifying schizophrenia. The proposed study demonstrates the applicability of alpha-EEG rhythm in a Gated-Recurrent-Unit-based deep learning model for studying schizophrenia.